2017
DOI: 10.26719/2017.23.8.534
|View full text |Cite
|
Sign up to set email alerts
|

Raising awareness of health care providers about MERSCoV infection in public hospitals in Mecca, Saudi Arabia

Abstract: Accroître la sensibilisation des prestataires de soins concernant l'infection MERS-CoV dans les hôpitaux de la Mecque (Arabie saoudite)RÉSUMÉ Pour les agents de santé, il est important d'avoir de bonnes connaissances, attitudes et pratiques concernant l'infection du MERS-CoV, notamment à la Mecque en raison des menaces que représentent cette infection pendant le pèlerinage (Hadj et Omra). L'objectif de la présente étude était d'évaluer les connaissances, attitudes et pratiques des prestataires de soins dans le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 20 publications
2
30
1
Order By: Relevance
“…The purpose of this study was to measure the level of preparedness of Saudi healthcare facilities to overcome COVID-19 pandemic and the level of knowledge of healthcare workers of the preparedness plan, although different public health policies were implemented in the last months, and the mandatory nature of these protective measures. Previous reports of Saudi healthcare facilities adherence to protective measures display that the level of information and education are related to a positive attitude toward infectious preventive practices (19). Of the 470 total hospital in Kingdome of Saudi Arabia (20), 25 designated hospital (20 Primary and 5 secondary) to endorse COVID-19 cases (Table 7) (11,15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The purpose of this study was to measure the level of preparedness of Saudi healthcare facilities to overcome COVID-19 pandemic and the level of knowledge of healthcare workers of the preparedness plan, although different public health policies were implemented in the last months, and the mandatory nature of these protective measures. Previous reports of Saudi healthcare facilities adherence to protective measures display that the level of information and education are related to a positive attitude toward infectious preventive practices (19). Of the 470 total hospital in Kingdome of Saudi Arabia (20), 25 designated hospital (20 Primary and 5 secondary) to endorse COVID-19 cases (Table 7) (11,15).…”
Section: Discussionmentioning
confidence: 99%
“…Globally, as of 6:30pm CEST, 19 May 2020, there have been 4,735,622 con rmed cases of COVID-19, including 316,289 deaths, reported to WHO (7,8). In Saudi Arabia, from Mar 2 to 6:30pm CEST,19 May 2020, there have been 59,854 con rmed cases of COVID-19 with 329 deaths (8). The Kingdome of Saudi Arabia (KSA) has well established healthcare facility and strict infection prevention control protocol (9,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For attitudes about pandemics, worry/fear/helplessness about pandemic (13, 14, 22, 28, 31, 33, 49, 51, 52, 60, 61, 63, 65, 68, 72, 76-78, 81, 83, 84), confidence in governments' ability to manage pandemic (13,23,28,30,33,41,61,63,65,68,70,77,78,82) and perceived severity of infection as a public health problem (13,29,39,41,44,45,59,65,70,72) was most commonly assessed. (Table 3) For practices in pandemics, behaviours related to mask utilization (14,16,23,26,28,30,32,33,35,38,40,48,59,61,63,65,70,73,80,82,(84)(85)…”
Section: Themes Identified From Items Used In Health Literacy Questiomentioning
confidence: 99%
“…In a study from Saudi Arabia of 228 trainees, half of the respondents indicated that their hospital had a clear plan while 28% did not feel that they were well prepared for MERS [72]. A targeted educational strategy increased HCWs' knowledge, skills and attitudes in private hospitals in Saudi Arabia [73]. Raising public awareness and recognition of the disease will also assist in preventing transmission [74].…”
Section: Discussionmentioning
confidence: 99%